Legal Protection of Communal Cultural Heritage in West Nusa Tenggara Through Registration of Communal Intellectual Property at the Ministry of Law of the Republic of Indonesia - Imran Imran; Gazali Gazali; Idarulhaq Idarulhaq (Abdi Masyarakat, 2026)
This community service article presents a qualitative study of legal protection efforts for communal cultural heritage in West Nusa Tenggara (NTB) Province through the registration of Communal Intellectual Property (CIP) at the Ministry of Law of the Republic of Indonesia. Employing a descriptive qualitative approach with phenomenological underpinnings, this study gathered data through participatory observation, open-ended written questionnaires, and systematic document analysis involving traditional community leaders, local government officials, legislative staff, and cultural practitioners from the Sasak, Samawa, and Mbojo communities. Findings reveal four interconnected themes: (1) the richness and vulnerability of NTB's communal cultural assets; (2) deep-seated misconceptions regarding the purpose of CIP registration; (3) structural and institutional barriers to registration; and (4) the critical importance of multi-stakeholder collaboration. The study concludes that sustainable CIP protection in NTB requires culturally sensitive legal education, institutional capacity building, and a robust multi-actor governance framework anchored in a provincial regulatory instrument. These findings offer significant implications for policy development and for community service practice in the domain of communal cultural heritage governance across Indonesia.